2018
DOI: 10.1016/j.adro.2018.06.004
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the potential benefit of reduced planning target volume margins for low and intermediate risk patients with prostate cancer using real-time electromagnetic tracking

Abstract: PurposeThe aim of this study is to quantify and describe the feasibility, clinical outcomes, and patient-reported outcomes of reduced planning target volume (PTV) margins for prostate cancer treatment using real-time, continuous, intrafraction monitoring with implanted radiation frequency transponder beacons.Methods and materialsFor this prospective, nonrandomized trial, the Calypso localization system was used for intrafraction target localization in 31 patients with a PTV margin reduced to 2 mm in all direct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 30 publications
(52 reference statements)
2
8
0
Order By: Relevance
“…Both studies showed that the intrafraction motion variance will continue to increase over time and are in good agreement with our results. Our findings are consistent with studies that assessed intrafraction motion with electromagnetic transponders [92], kV imaging [10,19], cine-MR [16] and transperineal ultrasound [68].…”
Section: Soft-tissue Prostate Intrafraction Motion Trackingsupporting
confidence: 91%
“…Both studies showed that the intrafraction motion variance will continue to increase over time and are in good agreement with our results. Our findings are consistent with studies that assessed intrafraction motion with electromagnetic transponders [92], kV imaging [10,19], cine-MR [16] and transperineal ultrasound [68].…”
Section: Soft-tissue Prostate Intrafraction Motion Trackingsupporting
confidence: 91%
“…Reduction in PTV margins can potentially reduce irradiated volumes and low dose spills considerably and may translate to clinical benefit. The reduction in PTV margins can reduce toxicities associated with radiation therapy as has been shown in some other disease sub-sites [ 18 , 19 ]. The standardization of IGRT protocol may reduce the chances of target miss during treatment with improving quality assurance of the whole process bettering outcome.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that PTV margins as low as 3 mm can be utilized for prostate treatments with the Calypso system. 8 When used in combination with endo‐rectal balloons (ERBs) that limit the prostate motion, the PTV expansion can be reduced to 2 mm. 9 Continual monitoring of the prostate position is also possible utilizing MRI Linacs, with a typical image refresh rate of ∼4 Hz.…”
Section: Introductionmentioning
confidence: 99%